Lymphovascular space invasion and Ki67 as predictors of lymph node metastasis in primary low grade serous ovarian cancer. Issue 1 (January 2021) - Grabowski, Jacek P; Glajzer, Joanna; Richter, Rolf; Plett, Helmut; Muallem, Mustafa‐Zelal; Braicu, Elena Ioana; Taube, Eliane; Sehouli, Jalid
Abstract : Objective : Low grade serous ovarian cancers characterize a unique clinical pattern and likely less frequent incidence of lymphatic metastasis. The expression level of Ki67 is associated with differences in prognosis and therapy outcome. However, its expression in combination with lymphovascular space invasion has not been evaluated in the prediction of lymphatic metastasis. Methods : Patients with low grade serous ovarian cancer were identified in an institutional database. Patients with primary low grade serous ovarian cancer diagnosed and/or treated at our center between September 2000 and December 2018 were identified. Receiver operator characteristics curve analysis was performed to find the cut‐off values of per cent Ki67 to discriminate patients with lymph node metastasis. The association between the presence of lymphovascular space invasion and lymph node involvement was analyzed. Results : A total of 109 patients with primary low grade serous ovarian cancer were identified in our institution's database. Of these, 72 (66.1%) patients underwent primary surgery with pelvic and para‐aortic lymph node dissection. Complete data for Ki67 expression and lymphovascular space invasion were obtained for 61 (84.7%) of these patients. Among them, 37 (60.7%) patients had lymph node metastasis. The presence of lymphovascular space invasion was associated with an increased risk of lymph node metastases (odds ratio (OR)=12.78, 95% confidence interval (CI) 3.15 to 51.81; p<0.001). In multivariate analysis including age >65 years, peritoneal carcinomatosis, and ascites>500 mL, lymphovascular space invasion remained a significant risk factor for lymphatic metastases (OR=35.11, 95% CI 2.38 to 517.69; p=0.010). Ki67 ≥6% was associated with a higher risk of lymphovascular space invasion (OR=3.67, 95% CI 1.26 to 10.64; p=0.017). No significant correlation between Ki67 expression level and nodal metastases was found (OR=2.19, 95% CI 0.76 to 6.26; p=0.14). Neither presence of lymphovascular space invasion or nodal metastases was associated with a statistically poorer prognosis. Conclusions : We showed an association between lymphovascular space invasion, Ki67 expression, and risk of lymph node metastasis in primary low grade ovarian cancer. Further prospective trials evaluating lymphovascular space invasion and Ki‐67 as predictors of lymph node metastasis are needed.